Research on Static and Dynamic Characteristics of Spindle System of High Speed Milling Machine - ZHANG Yuan; WANG Lifeng; ZHANG Jin (Journal of Harbin University of Science and Technology)
The performance of the spindle system has a great impact on machining accuracy and quality, so static and dynamic characteristics must be studied during design. In order to study the static and dynamic characteristics of the spindle system, a threedimensional model of the spindle system was established. The finite element method was used to analyze it to obtain the deformation, stress and strain, natural frequency and mode shape, and the impact of the change in bearing support stiffness was analyzed. Finally, experimental research is carried out. The results show that with the increase of bearing support stiffness, the amount of deformation gradually decreases and the natural frequency gradually increases; the resonance interval is around 815 86Hz, which does not cause resonance; the error is found to be less than 10% through experiments, which verifies the reliability of the simulation results. Subsequent research provided a favorable basis.